Communities in Perspective, A Literature Review of the Dimensions of Social Acceptance for Energy Development and the Role of Trust - Nourallah, Laura (Université d'Ottawa | University of Ottawa, 2016)
Social acceptance and support of energy projects at the community level is an important factor in determining energy development. Extensive literature has been written on the levels of public opposition to energy projects across different sectors, however none that covers a complete comparison between diverse sectors of energy production. Thus, the following section reviews the literature on factors relevant to social acceptance and support while looking at various sectors: renewable energy, hazardous facilities, and fossil fuels. The specific focus is accorded to the role of public confidence and trust in public institutions and authorities.
Keywords: Social acceptance; Energy; Regulation; Public Participation; Renewable energy; Communities and public policy